Prolactin Supplementation in Sperm Preparation A Study of Sperm DNA Fragmentation - Silvia W. Lestari (Journal of Global Pharma Technology, 2018)
One of the infertility management is performing intra uterine insemination (IUI), yet several reports indicated that the success rate is remained low. Sperm preparation, as one of contributing factor to IUI succeeds, has a possibility in generating on sperm DNA fragmentation. Recently, prolactin (PRL) is proved in enhance the sperm motility and protect the DNA integrity of the sperm. This study aimed to evaluate the efficiency of sperm preparation, in selecting sperm prior being utilized for IUI by PRL supplementation, based on the sperm DNA fragmentation. Semen samples were gained from 10 normozoospermic male who underwent sperm preparation for IUI. Semen analysis was performed to measure the sperm motility and velocity, before and after sperm preparation based on the WHO guideline. Samples were incubated at 500 ng (PRL 1), 750 ng (PRL 2), and 1000 ng (PRL 3). The Sperm Chromatin Dispersion (SCD) test was performed to evaluate the sperm DNA Fragmentation index (DFI). The percentage of motile sperm was higher in prepared sperm than in whole semen. PRL supplementation could not increase the percentage of motile sperm in sperm preparation by DGC method, while in SU method PRL worked uniquely in different concentration, since the lowest concentration performed the best result. The level of DFI after the supplementation of PRL was decrease in prepared sperm compared to the whole semen. PRL was proved to select the better sperm quality with decreased sperm DNA fragmentation in sperm preparation, particularly in moderate and severe DFI category.Keywords: Density gradient centrifugation, Prolactin, Sperm DNA fragmentation, Sperm motility, swim up.